Jaguars in the borderlands: Multinatural conservation for coexistence in the Anthropocene - Connolly, Erin; Nelson, Howard (Frontiers in Conservation Science, 2023)
Conservation in the human-dominated Anthropocene involves negotiations among diverse stakeholders. However, these stakeholder inclusion schemes are often superficial, leading to unsuccessful interventions. Here we apply the theory of multinaturalism as an operational starting point for stakeholder engagement efforts, to deepen local involvement and work towards coexistence. Multinaturalism posits that natures are multiple and can be known in many ways, and that many natures can coexist in the same geographical space. Using the northern jaguar population in the US-Mexico borderlands as a case study, we investigate, through semi-structured interviews, the natural realities (‘natures’) of various stakeholders involved in borderland jaguar conservation. We define a nature as an individual’s or group’s perceptions, knowledge, values, attitudes, and actions towards jaguars. We construct each stakeholder group’s natural reality of this jaguar population through applied thematic analysis, and we identify which aspects of stakeholders’ natures are similar and different, particularly across the international border. For example, we found that many conservationists and activists value the jaguar as an apex predator because its presence signifies ecosystem health and balance, while some ranchers hold existence value for the jaguar’s power and beauty, but resent its role as a predator, due to potential for conflict with livestock. This information provides a greater understanding of differences in realities that may cause conflicts over wildlife-related decisions, and can be used by local conservation actors to facilitate collaboration in a complex transboundary region. This interdisciplinary study highlights the importance of investigating the human dimensions of conservation completely, while treating all forms of knowledge about nature seriously and equally. Due to the unique nature of human-wildlife interactions, each conservation situation requires bespoke consideration, and particularly in diverse landscapes, a multinatural approach offers a novel path towards sustainable human-wildlife coexistence.